PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN TEKNIK TUTOR SEBAYA BERBANTUAN PICTURE AND PICTURE TERHADAP HASIL BELAJAR TIK SISWA KELAS VII SEMESTER GANJIL SMP NEGERI 1 SUKASADA - I Komang Gunadi (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
The study aimed at finding out (1) the effect of cooperative model with “tutor sebaya” technique and the helping of picture and picture towards learning achievement in communication and information technique of the students class VII SMP Negeri 1 Sukasada, (2) students’ responses towards the implementation of cooperative model with “tutor sebaya” technique and the helping of picture and picture. It was a quasi experimental study employing a Post-test Only Control Group  Design. The population of the study were all students class VII SMP Negeri 1 Sukasada in 2011/2012. The study involved a number of 81 samples consisting of students in class VII-D and VII-F. Class VII-F became an experimental group, while class VII-D as a control group. There were two different variables in this study, those are (1) independent variable: cooperative model with “tutor sebaya” technique and the helping of picture and picture, and (2) dependent variable: student learning achievement which can be definied by using descriptive statistic analyzes and also used the parametric Ttest. The findings indicated that (1) there was a significant  effect of cooperative model with “tutor sebaya” technique and the helping of picture and picture of the students. The average score of the students joining direct instruction was 32.49 with standard deviation of 3.96, and the average scores of the students joining cooperative model with “tutor sebaya” technique and the helping of picture and picture was about 37.75 with standard deviation of 4.52. It indicated that students joining cooperative model with “tutor sebaya” technique and the helping of picture and picture got higher scores than those a direct model, (2) the average value of students’ responses as about 74.35 and it shows the positive category through the implementation of cooperative model with “tutor sebaya” technique and the helping of picture and picture.